2013
DOI: 10.1089/cap.2012.0057
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Thoughts Are Associated with Platelet Counts in Adolescent Inpatients

Abstract: PLT counts are higher in suicidal hospitalized adolescents than in nonsuicidal inpatients, as well as than in controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…However, serotonin is carried by blood platelets and has been shown to exhibit seasonal fluctuation (21,22). A recent study even finds a direct relationship between platelet count and suicidal thoughts (32). In addition, a common variant in the neurogranin (NRGN) gene is associated with schizophrenia (33) and was identified as an intracellular platelet expressed gene highlighted by Gnatenko and colleagues (29).…”
Section: Discussionmentioning
confidence: 99%
“…However, serotonin is carried by blood platelets and has been shown to exhibit seasonal fluctuation (21,22). A recent study even finds a direct relationship between platelet count and suicidal thoughts (32). In addition, a common variant in the neurogranin (NRGN) gene is associated with schizophrenia (33) and was identified as an intracellular platelet expressed gene highlighted by Gnatenko and colleagues (29).…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 19 , 20 Patients with some psychiatric disorders have raised platelet counts. 18 , 21 Varsak et al 22 found that the NLR was significantly higher in first episode psychosis (FEP) versus control groups.…”
Section: Introductionmentioning
confidence: 99%
“…al. 2017; Ataoğlu and Canan 2009), and higher in hospitalized adolescents with suicidality than in non-suicidal inpatients and controls(Ragolsky et al 2013). Regarding coagulation potential, larger platelets have more granules and receptors and a greater tendency to clot than small platelets.…”
mentioning
confidence: 96%